The Mogul Emperors of Hindustan : AD 1398-AD 1707 - Holden, Edward S. (Brill | Manohar Publishers & Distributors, 2024)
This volume covers the brief history of the Mughal Empire stretching from the time of Timur, popularly known as Tamerlane, who invaded India in 1398 and defeated the last Tughluq ruler in Delhi. The book covers the history of the Mughals stretching from Babur, Humayun, Akbar, Jahangir, and Nur Mahal, or popularly known as Nur Jahan, Shah Jahan, and Aurangzeb. There are 13 illustrations in this book, primarily portraits of the rulers described in the volume. This book is a reprint of the 1895 edition.